Model Driven Engineering Languages and Systems 13th International Conference, MODELS 2010, Oslo, Norway 3-8, 2010, Proceedings, Part II - Petriu, Dorina C.; Petriu, Dorina C.; Rouquette, Nicolas.; Rouquette, Nicolas.; Haugen, Oystein.; Haugen, Oystein. (Programming and Software Engineering ;, 2010)
The MODELS series of conferences is the premier venue for the exchange of - novative technical ideas and experiences focusing on a very important new te- nical discipline: model-driven software and systems engineering. The expansion ofthisdisciplineisadirectconsequenceoftheincreasingsigni?canceandsuccess of model-based methods in practice. Numerous e?orts resulted in the invention of concepts, languagesand tools for the de?nition, analysis,transformation, and veri?cationofdomain-speci?cmodelinglanguagesandgeneral-purposemodeling language standards, as well as their use for software and systems engineering. MODELS 2010, the 13th edition of the conference series, took place in Oslo, Norway, October 3-8, 2010, along with numerous satellite workshops, symposia and tutorials. The conference was fortunate to have three prominent keynote speakers: Ole Lehrmann Madsen (Aarhus University, Denmark), Edward A. Lee (UC Berkeley, USA) and Pamela Zave (AT&T Laboratories, USA). To provide a broader forum for reporting on scienti?c progress as well as on experience stemming from practical applications of model-based methods, the 2010 conference accepted submissions in two distinct tracks: Foundations and Applications. The primary objective of the ?rst track is to present new research results dedicated to advancing the state-of-the-art of the discipline, whereas the second aims to provide a realistic and veri?able picture of the current state-- the-practice of model-based engineering, so that the broader community could be better informed of the capabilities and successes of this relatively young discipline. This volume contains the ?nal version of the papers accepted for presentation at the conference from both tracks.